A case report of an aneurysmal subarachnoid hemorrhage patient with negative Digital Subtraction Angiography could be detected by Computed Tomographic Angiography - ศรีแก้ว สุรเชษฐ์ (Journal of Medicine and Health Sciences, 2018)
Aneurysmal subarachnoid hemorrhage is a major devastating neurovascular diseae that brings the poor outcome and disability in most patients. The gold standard of investigation is digital subtraction angiography (DSA). The case report reveals an 72 years old woman with aneurysmal subarachnoid hemorrhage who could not be detected by DSA but could be diagnosed by computed tomographic angiography CTA brain.